Handbook of Indicators of Institutionalization of Academic Disciplines in SSH - Christian, Fleck; Victor, Karády (Serendipities. Journal for the Sociology and History of the Social Sciences, 2020)
This is the handbook of indicators with which the comparative research on the insitutionalization of several academic disciplines in the social sciences and humanities has been organised within the EU-funded project INTERCO-SSH. The project studied the historical trajectories of seven disciplines (anthropology, economcs, literature, philosophy, political science, psychology, sociology) in seven countries (Argentina, France, Germany, Hungary, Italy, the Netherlands, United Kingdom) since 1945.